Pengawasan Dewan Perwakilan Rakyat Daerah Terhadap Peraturan Kepala Daerah - Saputra, Agung; HB, Gusliana; Junaidi, Junaidi (Peneliti.net, 2024)
The constitution is all the provisions and basic rules regarding state administration. A country's existence cannot be separated from the underlying constitution. The supervisory function is one of the spirits of the people's representatives. Supervision is the main role or responsibility of DPRD in representing the community. Supervision must be carried out in a structured and good manner, so that the community is truly fulfilled in conveying their aspirations as well as controlling the work carried out by the government, in this case the regional head. From the results of the research it is concluded that First, Regulations on regional head regulations are regulated in the Minister of Home Affairs Regulation Number 120 of 2018 concerning Amendments to the Minister of Home Affairs Regulation Number 80 of 2015 concerning the Formation of Regional Legal Products. and Law Number 23 of 2014 concerning Regional Government. In the formation of governor regulations, there are two main types: those mandated by higher rules and those formed based on the authority of the regional head. The Riau Province Regional People's Representative Council (DPRD) has the authority to oversee the formation of gubernatorial regulations that are mandated by higher rules, while for gubernatorial regulations that are more related to autonomy functions, the DPRD has no obligation or right to oversee either the ratification or implementation. Second, Although each member of the DPRD has a supervisory function, their responsibilities are limited to commissions in public hearings without a special agenda for annual or semesterly supervisory meetings. Third,Regarding the ideal concept of regulation related to supervision of regional head regulations, considering that there are only general rules, it is necessary to make specific rules related to this supervision. This technical supervision can be made by the Minister of Home Affairs or by the regions themselves, considering that regional authority in regulating their own households has been legitimized through regional autonomy. In addition, technical regulations related to this supervision will strengthen the performance of the DPRD in legislation and supervision..